Ichthyofaunal diversity of Bansabati beel - An open wetland in Murshidabad, West Bengal: Fish diversity of Bansabati wetland - Mondal, Arghya Kamal; Srinivasan, Nagesh T.; Das, Sudhir Kumar; Behera, Samarendra; Das, Bipul Kumar; Abraham, T. Jawahar (Journal of the Inland Fisheries Society of India, 2023)
Information on ichthyofauna diversity is essential to manage and safeguard them and to sustain the health of an aquatic ecosystem. The present study investigated the ichthyofaunal diversity of Bansabati beel, an open wetland, in Murshidabad district of West Bengal. Fish were sampled every month to evaluate species diversity, abundance and trophic guild. A total of 42 fish species belonging to 21 families were recorded with the dominance of Cyprinidae. Carnivores (47%) dominated the trophic guild followed by omnivores (36%) and herbivores (17%). Three fish species were categorized in each of the "Vulnerable" and "Near threatened" groups on the IUCN Red List, while one fish species was categorised as "Endangered." Margalef’s richness index (4.334-5.423), Shannon-Wiener index (2.786 -3.018), Simpson’s diversity index (0.890 - 0.918) and Pilou’s evenness (0.795-0.817) values revealed that the beel has moderate to high fish diversity and evenness. However, it was also noted that the fish population in the beel has been steadily declining. In order to maintain biodiversity and reap long-term ecological advantages, the present study recommends ecosystem protection.